N-Heterocyclic Carbene Catalyzed Dynamic Kinetic Resolution of Pyranones - Zhao, Changgui; Li, Fangyi; Wang, Jian (Angewandte Chemie International Edition, 2016)
The dynamic kinetic resolution of 6‐hydroxypyranones with enals or alkynals through an asymmetric redox esterification is catalyzed by a chiral N‐heterocyclic carbene. The resulting esters are obtained in good to high yields and with high levels of enantio‐ and diastereocontrol. The reaction products are further derivatized to obtain functionalized sugar derivatives and natural products. Sweet products: The dynamic kinetic resolution of 6‐hydroxypyranones with enals or alkynals through an asymmetric redox esterification is catalyzed by a chiral N‐heterocyclic carbene (NHC). The resulting esters are obtained in good to high yields and with high levels of enantio‐ and diastereocontrol.